Pengembangan Modul Ajar Berbasis Problem Based Learning pada Materi Pewarisan Sifat untuk Fase D SMP - Khairani, Asmaul; Syamsurizal, H.; Arsih, Fitri; Rahmatika, Helsa (Lembaga Yasin AlSys, 2023)
Indonesia has implemented the Independent Curriculum in the 2021/2022 school year in several schools. Based on the results of observations, the lack of socialization makes it difficult for teachers to implement the Independent Curriculum, so teachers do not yet have complete teaching modules. This study aims to produce problem-based learning teaching modules for natural sciences in phase D of junior high school that are legible. This research is a development research that uses the 4D model with four stages, namely define, design, develop and disseminate. Due to time and budget constraints, this study only used three stages, namely define, design and develop. The subjects of this study were five natural science teachers as respondents. The object of this research is the problem-based learning module of inheritance for natural science subjects in phase D of junior high school. This study uses primary data types. The data analysis technique of this research is descriptive analysis technique and Likert scale. Based on the results of teacher observations, the development of teaching modules can be used as a solution. As much as 100% of teachers agreed to choose inheritance material to be used as the development of teaching modules. Based on the research, the inheritance teaching module was obtained with a readability value of 92.43%. It can be concluded that problem-based learning has been produced with inheritance teaching modules for natural science subjects in phase D of junior high school which read very well.